2000
DOI: 10.1046/j.1365-3040.2000.00553.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tree height on crown level stomatal conductance

Abstract: Variation in stomatal conductance is typically explained in relation to environmental conditions. However, tree height may also contribute to the variability in mean stomatal conductance. Mean canopy stomatal conductance of individual tree crowns (G Si ) was estimated using sap flux measurements in Fagus sylvatica L., and the hypothesis that G Si decreases with tree height was tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
264
2
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 297 publications
(283 citation statements)
references
References 55 publications
16
264
2
1
Order By: Relevance
“…Although transpiration accounting for~80% of LE in dry sites is not unheard of [Miller et al, 2010], we acknowledge that our lack of sap flux measurements over depth ranges within the sapwood and radial scaling of sap flux measurements contributed to errors in the sap flux data [Phillips et al, 1996;Schäfer et al, 2000]. Due to the increased number of large red maples and large bigtooth aspen trees in the control plot, these errors were likely greater in the control plot and would reduce the fraction of LE that is accounted for by E C in that plot.…”
Section: Red Oakmentioning
confidence: 97%
See 1 more Smart Citation
“…Although transpiration accounting for~80% of LE in dry sites is not unheard of [Miller et al, 2010], we acknowledge that our lack of sap flux measurements over depth ranges within the sapwood and radial scaling of sap flux measurements contributed to errors in the sap flux data [Phillips et al, 1996;Schäfer et al, 2000]. Due to the increased number of large red maples and large bigtooth aspen trees in the control plot, these errors were likely greater in the control plot and would reduce the fraction of LE that is accounted for by E C in that plot.…”
Section: Red Oakmentioning
confidence: 97%
“…On this basis, we expected an overestimation of E C of roughly 11% in the control plot and 3.7% in the treatment plot. Due to the dependence of radial patterns in sap flow on species, tree age, and site history and, therefore, the large variability among reduction factors, we chose to disclose this limitation rather than to assume the applicability of a reduction factor from existing literature that was not specific to our plots [James et al, 2002;Nadezhdina et al, 2002;Phillips et al, 1996;Renninger et al, 2013;Schäfer et al, 2000;Shinohara et al, 2013]. Despite these errors, the roughly 15% difference in transpiration between the control and treatment plots remains significant.…”
Section: Red Oakmentioning
confidence: 99%
“…To facilitate a comparison of G S response to D between the pre-and post-hurricane period, an evaluation of all predictions was made on data selected from scatterplots of G S versus D, based on a boundary line analysis (Martin et al 1997;Schäfer et al 2000). This was necessary because light measurements were not available for a conditional sampling of data in the posthurricane period.…”
Section: Daytime Responses Of G S To E L Q O and Dmentioning
confidence: 99%
“…10.3 reduces to g c = c*1/h (where c is a constant), which takes the shape of a non-linear decline in g c with pathlength. Both hydraulic and stomatal conductances follow this relationship (Mencuccini and Grace 1996b;McDowell et al 2002a;Niinemets 2002;Schäfer et al 2000). Thus far it has been shown that many structural factors vary with increasing h to minimize its impact on g c as trees grow larger, but that these homeostatic adjustments fail to completely offset the negative impact of h on g c (McDowell et al 2002a, b;Mencuccini 2003), in part due to requirements to protect xylem from irreversible embolism (Domec et al 2008).…”
Section: Introductionmentioning
confidence: 97%